Travel Bubble Policy Supporting between Thailand and Laos: Evidence from Tourist Market Integration Testing - CHUSAKUL, Wisitsiri; NONTHAPOT, Sakkarin (Journal of Environmental Management and Tourism; Vol 12 No 4 (2021): JEMT Volume XII Issue 4(52) Summer 2021DO - 10.14505//jemt.v12.4(52).09, 2021)
This paper examines international tourist market integration for international tourists from China, Japan, Malaysia, Korea and USA visiting Thailand and Laos for supporting the travel bubble policy. These are being integrated to be offered as a single destination, using quarterly data from 2001 to 2019. The cointegration test of the ARDL approach assesses the number of international tourists. The results of the research show that the tourism markets of Thailand and Laos are integrated. In the short run, international tourists from China and Malaysia who visit Laos also visit Thailand.  Bi-directional causality was evident for tourists from Japan, Korea and the USA. For long run causality, tourists from Japan, Malaysia, Korea and the USA who visit Laos also visit Thailand. Therefore, we can confirm that both Thailand and Laos follow the single destination policy and both countries are complementary tourism destinations for international tourists. Therefore, this study confirms that Thailand and Laos can be launch the travel bubble policy. The Thailand and Laos governments should target tourism markets by travel bubble policy with special protocols that is designed to improve competitiveness or to enhance tourism market efficiency.